The Effect of Workload, Work Discipline, and Work from Home System on Employee Performance During the Covid-19 Pandemic - Bua, Christian Nataniel Tandi; Krisnandi, Herry; Digdowiseiso, Kumba (International Journal of Social Service and Research, 2024)
Human resources play a crucial role in supporting organizational dynamics, relying on collaboration and continuous activities. However, the COVID-19 pandemic has disrupted normal operations, particularly impacting the Secretariat of the PPSDMP Agency of the Ministry of Agriculture. As public servants, they must navigate through increased workloads due to limitations imposed by the pandemic. Employees' work discipline has faced challenges as health concerns take precedence, contributing to a shift to a work-from-home system, unfamiliar to many. This study investigates the impact of Workload, Work Discipline, and the Work From Home System on Employee Performance during the pandemic. Utilizing primary data from 110 employees through questionnaires, the analysis, employing multiple linear regression in SPSS 25.0, indicates a positive and significant effect of Workload, Work Discipline, and the Work From Home System on Employee Performance. The study suggests that government agencies should prioritize these factors to enhance employee performance, recommending adjustments in workload and reinforcing work discipline amidst the ongoing challenges posed by the COVID-19 pandemic. Additionally, it emphasizes the need for accommodating the new work system, particularly for employees unfamiliar with technology, as a cultural shift to improve overall performance during these challenging times.